Optical properties of monolayer transition metal dichalcogenides probed by spectroscopic ellipsometry - Liu, Hsiang-Lin; Shen, Chih-Chiang; Su, Sheng-Han; Hsu, Chang-Lung; Li, Ming-Yang; Li, Lain-Jong (Applied physics letters, 2014)
Spectroscopic ellipsometry was used to characterize the complex refractive index of chemical-vapor-deposited monolayer transition metal dichalcogenides (TMDs). The extraordinary large value of the refractive index in the visible frequency range is obtained. The absorption response shows a strong correlation between the magnitude of the exciton binding energy and band gap energy. Together with the observed giant spin-orbit splitting, these findings advance the fundamental understanding of their novel electronic structures and the development of monolayer TMDs-based optoelectronic and spintronic devices.